Study on optimizing technology and physicochemical properties of coix bran dietary fiber prepared by enzymatic method - LIN Tinglong; ZOU Lan; PAN Xiaowei; LIU Yuanjing (Shipin yu jixie)
Objective: The study aimed to optimize the preparation process and investigate the quality of coix bran dietary fiber. Methods: The coix bran was used as raw material; the effects of solid-liquid ratio, the amount of amylase and alcalase on the extraction rate were analyzed by usingorthogonal experiments. The chemical composition and physicochemical properties of the dietary fiber obtained under the optimal preparation conditions was analyzed. Results: The optimal extraction parameters of dietary fiber were as follows: solid-liquid ratio was 1∶10 (g/mL), the amount of amylase and alcalase was 100 U/g, respectively, and the extraction rate was up to 84.39%. The insoluble dietary fiber (64.49%) was significantly (P ＜ 0.05) improved compared to coxi bran. And the soluble dietary fiber was 0%, the content of moisture, fat, starch, and protein was significantly decreased (P ＜ 0.05). When the temperature increased, swelling capacity, water holding capacity and oil holding capacity were improved. and was 3.12 mL/g, 4.02 g/g and 4.29 g/g, respectively. Conclusion: The method could be used as a reliable method to extract the coix bran dietary fiber.